Experimental investigation of pool fire behavior to different tunnel-end ventilation opening areas by sealing. (March 2017) - Chen, Chang-kun; Xiao, Huang; Wang, Nan-nan; Shi, Cong-ling; Zhu, Cong-xiang; Liu, Xuan-ya
Graphical abstract: Highlights: Reduced-scale experiment on tunnel fire by sealing with varied ratios was done. Temperature inside tunnel and near portal and mass loss rate of fuel were obtained. Response behaviors of burning, smoke layer, flame jet, etc. were observed. Heat loss and heat produced related to sealing ratio affect tunnel temperature. A critical sealing ratio related to the fuel area was found. Abstract: A series of experimental tests were conducted in a 1/9 reduced-scale tunnel to investigate the effect of sealing ratio (which is equal to the sealing height divided by the tunnel entrance height) on combustion process and temperature field of liquid pool fires in tunnel using methanol as fuel. The two tunnel entrances were sealed symmetrically with different ratios (such as 0%, 25%, 50%, 75% and 100%) in the tests. In addition, fuel area was also considered. Temperatures inside tunnel and near the entrance were measured together with the mass loss rate of fuel. The results demonstrate that during the sealing process, the ceiling temperature inside tunnel varies versus sealing ratio, which is primarily due to the comprehensive effect between the heat loss by the hot smoke flowing out of tunnel entrance and the heat produced by combustion significantly related to ventilation, and both the above two factors are related to the open area of tunnel entrance. The possible depression effect related to the fuel area of sealing on combustion was observed in the experiment. Moreover, there exists a critical sealing ratio closely related to the fuel area, at which the ceiling temperature inside tunnel would reach the maximum. And the larger the fuel area is, the lower the critical sealing ratio would be. Additionally, the dimension and temperature of the fire plume near tunnel entrance, which is always a serious threat to the firefighters in real tunnel fire, were also obtained and analyzed.